Characterization and Properties of Sodium Hexa-Fluorosilicate and its Potential Application in the Production of Sodium Fluoride - Arianpour, Farzin; Arianpour, Aslı Çakır; Aali, Behnam (Springer Science and Business Media LLC, 2020)
Sodium hexa-fluorosilicate (Na2SiF6) is a synthetic inorganic material with distinguished chemical, thermal and optical properties. In this research, a pure sodium hexa-fluorosilicate sample was systematically investigated via various characterization techniques. The amounts of constitutional elements and impurities were investigated using X-ray fluorescence and the chemical purity was determined as 99.89 wt%. Physical properties were calculated as 2.7085 g/cm3 for density, 0.98 m2/g for specific surface area and a mean particle size (D50) of 77.3 μm. Thermal analysis was applied to understand the degradation of Na2SiF6 till 900 °C. The mineral composition and morphology was studied using X-ray diffraction, scanning and transmission electron microscopy and revealed the existence of P321 type hexagonal structure associated by elongated prism shaped precipitated crystals. Spectroscopy studies were performed via different techniques at different ranges of measurement. Thermal stability was investigated by post-mortem phase analysis of heat treated Na2SiF6 samples and showed a well stability till 400 °C. It is proposed that the thermal dissociation of Na2SiF6 can be utilized as a facile, inexpensive and green way for the synthesis of sodium fluoride instead of routine hydrofluoric acid-based methods. The obtained results suggested that the examined sodium hexa-fluorosilicate material could potentially be used as a reliable precursor in the synthesis of fluoride and silicon based materials due to its acceptable physical properties, chemical purity and thermal behavior.